Effects of the naturally‐occurring disaccharides, palatinose and sucrose, on incretin secretion in healthy non‐obese subjects. Issue 3 (13th February 2013) - Maeda, Aya; Miyagawa, Jun‐ichiro; Miuchi, Masayuki; Nagai, Etsuko; Konishi, Kosuke; Matsuo, Toshihiro; Tokuda, Masaru; Kusunoki, Yoshiki; Ochi, Humihiro; Murai, Kazuki; Katsuno, Tomoyuki; Hamaguchi, Tomoya; et al.
Abstract: Aims/Introduction: Incretins might play some pathophysiological role in glucose metabolism in diabetes and obesity; it is not clear whether or not the amount and the pattern of incretin secretion vary with different types of sugars. To evaluate the effect of two types of disaccharides on glucose metabolism and the kinetics of incretin secretion, plasma levels were measured after palatinose or sucrose ingestion in non‐obese healthy participants. Materials and Methods: The study was carried out on healthy participants who were given a solution containing 50 g of palatinose or sucrose for ingestion. Blood samples were obtained before loading and after ingestion. Insulin, glucagon and incretins hormones were measured by the enzyme‐linked immunosorbent assay method. Results: When the data were compared between palatinose and sucrose ingestion, both plasma glucose values at 15, 30 and 60 min, and plasma insulin values at 15 and 30 min after palatinose loading were significantly lower than those after sucrose loading. Plasma levels of total glucose‐dependent insulinotropic polypeptide at 15–90 min after palatinose loading were significantly lower than those after sucrose loading. Plasma levels of total and active glucagon‐like peptide‐1 at 90 min and the area under the curve (60–120 min) of the total glucagon‐like peptide‐1 were significantly higher with palatinose‐loading than with sucrose loading. Conclusion: Compared with sucrose, palatinose appears to have a more favorable effect on glucose metabolism and protection of pancreatic islets as a result of less hyperglycemic and hyperinsulinemic potency.